Exploring the ideas of hyper local news as a future journalism - Mior Kamarulbaid, Afiqah; Wan Abas, Wan Anita; Omar, Siti Zobidah; Bidin, Rosmiza (Global Academic Excellence, 2019)
This study is to explore the ideas of hyperlocal news as future journalism. As the economy weakens, the general trend of declining circulation and advertising revenue for the past few years, Malaysia's media industry has begun downsizing or wrapping up certain segments of their operations. Utusan Melayu offers VSS to more than half its workers as part of its restructuring exercise to reduce overall costs due to the company's financial constraints, the same goes for Media Prima and Astro. The new media on news platforms has changes the practices of news making. Growing body research on digital journalism and news on digital media but little has been undertaken into the potential of hyperlocal news as future journalism. In this paper, researcher review articles related to the study of hyperlocal news, digital journalism and new media. By conducting this study, a deeper understanding of what is hyperlocal media, what the roles and how this hyperlocal media as a future of local journalism.